A non-invasive ultra-wide band based system using artificial intelligence to determine blood glucose level / \c Md Shawkat Ali. - Ali, Md Shawkat (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The aim of this research is to develop an Ultra-wide Band (UWB) and Artificial Intelligence (AI) based system application to determine blood glucose concentration level non-invasively. To achieve this aim following objectives are set ; to investigate on UWB antennas and body parts, which can be best suited for reliable blood glucose detection ; to develop a system model using optimized neural network for auto-analysis of UWB pulse to obtain blood glucose level ; to integrate the hardware as UWB antenna and software as optimized neural network to compare the actual blood glucose level.